Design of the nanopositioning and mechanical system for cavity-based X-ray free electron laser. Issue 1 (1st December 2022) - Shu, Deming; Kearney, Steven; Anton, Jayson; Mashrafi, Sheikh; Shvydko, Yuri; Lindberg, Ryan; Jansma, William; Toter, William; Shi, Xianbo; Assoufid, Lahsen; White, Marion; Fak Tan, Tien; et al.
Abstract: With forming of an X-ray cavity with a set of narrow bandwidth diamond Bragg crystals and by storing and recirculating the output of an amplifier in an X- ray cavity so that the X-ray pulse can interact with following fresh electron bunches over many passes thus enabling the development of full temporal coherence, we will be able to build cavity-based X-ray FELs (CBXFELs) such as the X-ray free-electron laser oscillator (XFELO) and the X-ray regenerative amplifier free-electron laser (XRAFEL) [1, 2]. One of the key challenges to forming the X-ray cavity is the nanopositioning design and construction of the cavity mechanical system. In this paper, we present the design of the nanopositioning and mechanical system that is currently under construction for use in a proof-of-principle cavity-based X-ray free electron laser experiment at the LCLS-II at SLAC.